Dinuclear Lanthanide Compound as a Promising Luminescent Probe for Al3+ Ions - Zhi Chen; Yinghao Xie; Zhanbo Li; Tao Lin (Molecules, 2022)
Luminescent probes have wide applications in biological system analysis and environmental science. Here, one novel luminescent dinuclear europium compound with a crown ether analogous ligand was synthesized through a solvent–thermal reaction. Through transformation, upon the addition of Al3+ ions to the N,N′-dimethyl formamide solution of the europium compound, the luminescent intensity of the characteristic emission of Eu3+ decreased, and a new emission peak appeared at 346 nm and increased rapidly. The luminescent investigation indicated that it could act as a highly sensitive and selective luminescent probe for Al3+ ions. Moreover, mass spectrometry and single-crystal X-ray diffraction confirmed the formation of a new more stable trinuclear aluminium compound during the sensing process.